THE ESTABLISHMENT AND ACTIVITY OF THE PROSVITA SOCIETY IN VOLYN: OVERVIEW OF MODERN UKRAINIAN HISTORIOGRAPHY (Південний архів (історичні науки), 2023)
Aims. To analyze the state of scientific development of the formation and activity of Enlightenment Organizations (named Prosvita) in Volyn in the works of modern Ukrainian researchers. Methods. The research was conducted on the basis of using the principles of historicism, objectivity and comprehensiveness of sources using methods: historiographical analysis and synthesis, problem-chronological, problem-situational and comparative. Results. On the basis of the mentioned principles and methods, the historiographic work on the history of the Prosvita society in Volyn was analyzed. A review of historiography allowed us to conclude that this issue attracts the attention of a significant number of scientists and local historians, primarily from Lutsk, Rivne and other cities of Western Ukraine. Conventionally, the main works (monographs, dissertations, scientific collections and articles) are divided into two groups: formation and development of Enlightenment Organizations in Volyn and directions of activity of the Volyn “Prosvitas”. Among the first group, it is worth noting researchers V. Baran, M. Kucherepa, S. Ponomarenko, B. Savchuk, L. Strilchuk, M. Filipovych, and others, and in the second – О. Kalishchuk, L. Ponedelnyk, T. Sladkovska, Yu. Soroka, and others. On the basis of historiographical analysis, it has been established that the majority of scientists emphasize the multidimensionality of the activities of the Volyn Enlightenment Organizations and their important role in the national and cultural development of Ukraine. Conclusions. Modern Ukrainian researchers deepen the study of the history of the Enlightenment movement in Ukraine. In recent years, the number of works on the history of the Prosvita in the regional dimension has increased. The problem of formation and directions of activities of Enlightenment Organizations in Volyn arouses considerable interest among scientists. The analysis and presentation by the authors in the studies of the forms and methods of activity of local Enlightenment centres contributes to the educational work of modern public organizations, and this, in turn, creates favorable conditions for the popularization of the Ukrainian language and culture. The analysis and presentation of the forms and methods of activity of local Enlightenment Organizations by the authors in the research contributes to the educational work of modern public organizations, and this, in turn, creates favorable conditions for the popularization of the Ukrainian language and culture. Today, this is extremely important for the formation of national consciousness, identity and, in general, the national and cultural development of Ukraine.
Keywords: Prosvita, Enlightenment Organizations, Volyn, historical review, scientific research